Making Sense of Neoliberalism in Aotearoa/New Zealand: A Response to Nicholls, Duncan, Neilson, and Foucauldian Governmentality - Roper, Brian (New Zealand Sociology, 2026)
This article provides a new and original consideration of the contemporary relevance and usefulness of approaches that deploy conceptions of neoliberalism to make sense of Aotearoa/New Zealand’s changing economy, society, and polity since 1984. In the aftermath of the global financial crisis, an article of mine focused on the Fifth National Government was published in New Zealand Sociology, with ‘responses to Roper’ by Duncan, Nicholls, and Nielson appearing in the following issue. Among other things, this symposium discussed whether: (1) conceptions of neoliberalism were about to become less relevant; (2) the entire period of New Zealand’s political history from 1984 to the present is best understood using a conception of neoliberalism as an ‘analytical lens’; and (3) there are foreseeable future developments that might bring the dominance of neoliberalism to an end. These issues frame my consideration of the contributions by Duncan, Nicholls, Neilson, and those who use Foucauldian governmentality as an analytical lens to analyse neoliberalism. The key takeaways are that there has been a large increase in scholarship focused on neoliberalism, Foucault, capitalism, Marx, and Marxism since 2008, historical materialism continues to provide sound heuristic guidance for analysing neoliberalism, New Zealand’s political history from 1984 to the present is best understood as centrally involving the rise, modification, and entrenchment of a neoliberal policy regime, and neoliberalism is likely to remain entrenched despite resistance from the left and challenges from the far right.